ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN TAHUN 2013-2016 (Studi Empiris pada Perusahaan Manufaktur Subsektor Industri Otomotif dan Komponen, Subsektor Makanan dan Minuman, dan Subsektor Farmasi) - Diva Ayu Imanda Sari, 15.05.62.0023; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
This research performed to examine influence of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), Firm Size, and Firm Growth on Dividend Payout Ratio (DPR) as an independent variabel. Sample for this research were taken using a purposive sampling method from manufacturing companies subsector automotive and component, subsector food and beverage, and subsector of pharmaceutical listed on Indonesia Stock Exchange (BEI) period from 2013 until 2016. Analyze technique that use in this research is multiple regression analysis. The results of this research indicate that Return on Asset (ROA) have significantly positive influence on Dividend Payout Ratio (DPR). Whereas Current Ratio (CR), Debt to Equity Ratio (DER), Firm Size, and Firm Growth hasn’t correlation influence towards Dividend Payout Ratio (DPR).Keywords: Manufacturing Industry, Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), Firm Size, Firm Growth on Dividend Payout Ratio (DPR)